Firefly Algorithm for adaptive emergency evacuation center management - Yusof, Yuhanis; Hashim, Nor Laily; Che Pa, Noraziah (The Science and Information Organization, 2016)
Flood disaster is among the most devastating natural disasters in the world, claiming more lives and causing property damage.The pattern of floods across all continents has been changing, becoming more frequent, intense and unpredictable for local communities.Due to unforeseen scenarios, some evacuation centers that host the flood victims may also be drowned.Hence, prime decision making is required to relocate the victims and resources to a safer center.This study proposes a Firefly Algorithm (FA) to be employed in an emergency evacuation center management. Experimental analysis of a minimization problem was performed to compare the solutions produced by FA and the ones generated using Tabu Search. Results show that the proposed FA produced solutions with smaller utility value, hence indicating that it is better than the benchmark method.